Are Violent Delinquents Worth Treating? A Cost-Benefit Analysis - Caldwell, Michael F. (Journal of research in crime and delinquency, 2006)
This study reports on the cost benefits of an intensive treatment program for unmanageable juvenile delinquent boys, compared to the usual treatment in a secured juvenile corrections facility. A total of 101 boys who received the majority of their treatment services in a specialized program providing intensive mental health treatment were matched to a group of 101 juveniles who received treatment as usual (TAU) in a secured juvenile corrections setting on the basis of treatment propensity scores. Outcome data included the number and type of criminally charged offenses over an average follow-up period of 53 months (range 14 to 92 months). Borrowing from Cohen criminal justice processing costs for each offense was calculated in 2001 dollars. The initial costs of the program were offset by improved treatment progress and lowered recidivism, especially violent recidivism. The treatment group yielded a benefit-cost ratio of more than 7 to 1 over the TAU group. The results are discussed and compared to cost-benefit analyses of other juvenile treatment programs. [ABSTRACT FROM AUTHOR]